Kiprah Dakwah Tengku Teuku Abdul Rahman Kaoy - Arifin - Zain; Maturidi - Maturidi (Fakultas Dakwah dan Komunikasi UIN Sunan Gunung Djati Bandung, 2022)
Tengku Teuku Abdul Rahman Kaoy is a preacher from Aceh who devotes all his ideas, thoughts and time to the advancement of da'wah. This study aims to determine how the implementation, thought and da'wah movement of Tengku Teuku Abdul Rahman Kaoy. This study uses a qualitative research method with a character study approach. The results show that Tengku Teuku Abdul Rahman Kaoy can be categorized as one of the da'wah figures in Aceh with several considerations; first, he has devoted all his time and life to carrying out da'wah, both verbally, in writing and by good examples for the people around him. Second, he has good ideas in the field of da'wah and has succeeded in realizing these ideas by establishing several da'wah organizations, such as HIMDA (Himpunan Masyarakat Pencinta Dakwah) and ISKADA (Ikatan Siswa Kader Dakwah) which still survive to this day and have produced thousands of cadres da`i. Third, Rahman is known as a preacher who dedicates his knowledge to the benefit of the wider community and academically has been a lecturer at the Faculty of Da'wah and Communication at UIN Ar-Raniry who studies da'wah from a scientific point of view and this is an added value that is rarely owned by others. The impact of this research is expected to enrich the treasures of da'wah both in terms of methods and content, especially those related to the da'wah thinking and da'wah movement of Tengku Teuku Abdul Rahman Kaoy.